Development Of Nanostructured Gas Sensing Material As An Ethylene Gas Detector - Akhir, Maisara Azad Mat (2016)
Ethylene gas is an important substance in fresh argo-products marketing because it can be used commercially for artificial plant hormone and to monitor the ripening process of climacteric fruits. Realizing the importance of ethylene gas sensor for fruit ripening process, many studies have been carried out in order to investigate the influence of ethylene to the ripening process. Tin oxide (SnO2) nanoparticles are the most popular material for ethylene gas sensor due to its wide band gap n-type semiconductor properties, which leads to low electrical resistance and better electrical conductivity for gas sensing properties. Furthermore, low operating temperature, high sensitivity, mechanical simplicity of sensor design and low manufacturing cost have made SnO2 the preferred choice for gas sensor applications. In this work, chemical vapor deposition (CVD) and hydrothermal methods were utilized to synthesize SnO2 nanostructures (NSs). The synthesis, material characterizations and the gas sensing properties of SnO2 NSs against ethylene gas had been studied. Firstly, SnO2 nanowires (NWs) were grown on silicon substrates by using CVD method. The effects of different synthesis conditions (growth temperature, growth duration, flow rates of argon and oxygen) on SnO2 NWs dimensions were investigated by using statistical DOE. Scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction spectroscopy (XRD) characterizations confirmed the successful fabrication of SnO2 NWs. From the response surface plot with DOE, the smallest SnO2 NWs diameter (~46 nm) was obtained at a reaction temperature of 850 °C with the oxygen / argon flow rates 50 sccm / 100 sccm, respectively and deposition time of 60 minutes. On the other hand, the largest SnO2 NWs diameter (~160 nm) was produced at temperature of 900 °C. From perturbation analysis, it was found that temperature gave the most significant effect to the diameter of SnO2 NWs followed by growth duration and flow rates of argon / oxygen. Later, SnO2 nanorods, nanocubes and nanospheres were obtained by a hydrothermal method. The effects of synthesis parameters (precursor concentration, reaction temperature, reaction duration and palladium concentration) on crystal structure, morphology, particle size and band gap properties were studied. From the perturbation plot with DOE, crystal size of SnO2 NSs was mostly affected by hydrothermal temperature followed by treatment duration, SnCl4.5H2O molar concentration and Pd concentration. For ethylene gas sensing characterization, SnO2 NSs produced by CVD and hydrothermal methods were tested for gas sensing properties towards the low concentrations of ethylene gas. From the testing, it can be found that, SnO2 NSs produced by hydrothermal technique had shown the most excellent sensing performance in terms of sensitivity, optimum operating temperature and reversibility feature than SnO2 NWs produced by CVD route. On the other hand, CVD sample with the smallest NWs diameter has the quickest response and recovery times which are less than 10 seconds (s) and less than 1 minutes respectively to ethylene gas than the sensors produced by hydrothermal, although the sensitivity is lower than hydrothermal samples.